Problematika Pendidikan Kristen Di Indonesia Di Tengah Kemerosotan Moral - Hendrik Legi; Herdianto Sibarani (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2023)
Morals in Christian education are an important aspect in shaping the character of students based on Christian principles and values. Christian Education aims to introduce students to Christian values such as love, mercy, justice, and integrity, and guide them in applying these values in everyday life. It includes understanding Christian teaching, moral character building, and developing Christian ethics. Students are taught how to understand and apply Christian values in their decision-making and behavior. In addition, they are encouraged to engage in personal reflection and prayer as a way to seek God's guidance in their actions. Social service is also an integral part of Christian moral education, where students are taught to help others in society. Christian moral education uses case studies of moral dilemmas to stimulate students' discussion and critical thinking. Through close cooperation between schools, families, and churches, consistency in the teaching of Christian values is maintained. Morals in Christian education form a solid basis for Christian individuals in dealing with complex moral situations and taking decisions in accordance with the principles of Christianity. This approach is instrumental in shaping the ethical, responsible, and loving character of the Christian individual in a changing modern society.